Genesis of Flea-Born Transmission of Plague Microbe, Yersinia pestis: Two Approachs – Molecular-Genetic and Ecological Ones - V. V. Suntsov (Проблемы особо опасных инфекций, 2018)
Two approaches to studying the origin and transmission mechanism of the flea-borne plague pathogen, Yersinia pestis: molecular-genetic and ecological ones – are considered in this review. The molecular genetic approach is based on saltation evolutionary ideology and relies upon the phenomenon of horizontal gene transfer of pla and ymt as critical evolutionary events. Further deletion of some structural and regulatory genes optimized “blockage” mechanism of transmission. The Ecological approach is based on the modern synthetic theory of evolution. It posits a gradual population-genetic transformation in the Marmot – Flea (Marmota sibirica – Oropsylla silantiewi) transitional (heterothermal, heteroimmune) host-parasite system in Late Pleistocene – Holocene epochs. The best prospects for disclosing the mechanisms of evolutionary formation of flea-borne Y. pestis transmission consist in the synthesis of molecular-genetic and ecological approaches.